2004
DOI: 10.1055/s-2004-861576
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Synovium in Rheumatoid Arthritis

Abstract: Early diagnosis, followed by early initiation and optimal adjustments of aggressive therapies, are acknowledged as essential to optimize long-term clinical and radiological outcome in rheumatoid arthritis (RA). This requires sensitive methods for detection and monitoring of the primary feature of RA--the synovitis. In comparison with conventional methods, magnetic resonance imaging (MRI) offers assessment of the rheumatoid synovium with improved sensitivity to early pathology and to change. Various aspects suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…MRI signs of synovitis are related to increased thickness/volume, increased signal intensity after intravenous gadolinium injection ("enhancement"), and increased water content, alone or in combination 24 . The importance of deploying CE-MRI for assessment of synovitis in OA has recently been recognized 9 .…”
Section: Scoring Methods For Mri Evaluation Of Synovitis In Knee Oamentioning
confidence: 99%
See 2 more Smart Citations
“…MRI signs of synovitis are related to increased thickness/volume, increased signal intensity after intravenous gadolinium injection ("enhancement"), and increased water content, alone or in combination 24 . The importance of deploying CE-MRI for assessment of synovitis in OA has recently been recognized 9 .…”
Section: Scoring Methods For Mri Evaluation Of Synovitis In Knee Oamentioning
confidence: 99%
“…Although non-CE-MRI is still the most commonly used modality to assess synovitis in OA clinical studies 24,25,37,38 , findings from CE-MRI studies have demonstrated the limitations of non-CE-MRI for evaluation of synovitis 11e13,20,23,36,39e43 . One clear advantage of CE-MRI over non-CE-MRI is its ability to differentiate inflamed synovium from joint effusion.…”
Section: Ce-mri Evaluation Of Synovitis In Knee Oa and Associations Wmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, magnetic resonance imaging (MRI) and ultrasonography (US) are now used for synovitis evaluation in RA [2,3]. These diagnostic imaging techniques are useful for early diagnosis and prediction of joint destruction, because they are able to identify synovitis with greater sensitivity and accuracy than physical findings [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of MRI in diagnosing early RA is improving, since it shows greater sensitivity than radiography in detecting synovitis [6,14,15]. However, evaluations based on MRI images are occasionally difficult and time consuming.…”
Section: Introductionmentioning
confidence: 99%